The Dependency of the Jordanian Journalists on Mobile in News Production - Tahat, Khalaf; Hatamleh, Shatha (Dirasat: Human and Social Sciences, 2022)
This study aims to investigate how much Jordanian journalists depend on mobile phones to produce media content, it also aims to investigate the reasons stand behind using mobile in the media and the required skills that journalists need to produce media content. The researchers used a questionnaire as a tool to collect the data from (151) Jordanian journalists by using a simple random sample. The main findings of this study were: The overwhelming majority (63%) of the sample depend heavily on mobile journalism to produce media content. The results also showed that the main reason to use the mobile journalism to produce media content was the accuracy and the quickness offered by mobile phones (4.36 out of 5). - The results found that editing news was the most used motivation for Jordanian journalists in producing media content(61%) . The most important required skills that used to produce media content was the fact that mobiles able journalists to shoot video and edit it (4.28 out of 5).